2018
DOI: 10.18203/2349-3291.ijcp20182572
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and outcome of diphtheria in central India: a retrospective observational study

Abstract: Background: Although, diphtheria is eliminated by many developed countries by effective immunization, still diphtheria   continues to be endemic in India and leading cause of morbidity and mortality, especially in areas in the border of the two states. The objective of the present study was to recognize the clinical profile, morbidity and mortality pattern of diphtheria and to study their immunization status as a retrospective observational study performed in pediatric wards and paediatric intensive care unit.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 12 publications
5
18
0
Order By: Relevance
“…Of 29 cases with myocarditis, 14(77.7%) succumbed due to underlying ventricular tachycardia and cardiogenic shock. Jayashree et al, reported 32 patients with myocarditis of which 25(78.1%) died, similar results were obtained by Meshram et al 13,9 In this study, it was observed that inadequate immunity and prolonged illness had significant association with development of myocarditis. Thus, re-emphasizing the role of early diagnosis and prompt management of this dreadful disease, which may further ameliorate the subsequent development of such devastating complication in these patients.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Of 29 cases with myocarditis, 14(77.7%) succumbed due to underlying ventricular tachycardia and cardiogenic shock. Jayashree et al, reported 32 patients with myocarditis of which 25(78.1%) died, similar results were obtained by Meshram et al 13,9 In this study, it was observed that inadequate immunity and prolonged illness had significant association with development of myocarditis. Thus, re-emphasizing the role of early diagnosis and prompt management of this dreadful disease, which may further ameliorate the subsequent development of such devastating complication in these patients.…”
Section: Resultssupporting
confidence: 87%
“…similar to reports from different centres (32-56.3%) in north India. 9,17 Late presentation when complications had already been set in, delayed ADS administration, financial constraints by care givers attributed to high case fatality rate in this series. This study made an important observation with regards to immunization status and disease related morbidity and fatality, as complete survival was observed in fully immunized group.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The clinical manifestations can vary from mild to severe to the life threatening depending on immune status of host and severity of infection [12]. In the present study, 6 year old boy had fever, throat pain, neck swelling, difficulty in breathing and membrane over tonsil.…”
Section: Discussionmentioning
confidence: 54%
“…There have been several recent reports of outbreaks and newspaper articles highlighting the seriousness of the present situation, which emphasizes the role of the public, healthcare workers, and governments in order to control and prevent the spread of diphtheria [19][20]. A local newspaper published (in the Telegu language) a picture of parents and relatives carrying and transporting a pediatric patient to a better medical facility whose condition worsened with suspected diphtheria, as shown in Figure 7.…”
Section: Indian Scenario Of Diphtheriamentioning
confidence: 99%